Analisis Liability Protection Nasabah dalam Kasus Malfungsi Aplikasi Mobile Banking Bank Syariah Indonesia Perspektif Imam Abu Hanifah - Fadlan Al Mahalli; Tetty Marlina Tarigan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The development of digital banking has presented new challenges in customer protection, especially related to malfunctions in mobile banking applications that have the potential to harm customers. The phenomenon of BSI Mobile system disruptions throughout 2023-2024 shows the urgency of an in-depth study of the liability protection mechanism in accordance with sharia principles. This study aims to analyze the implementation of BSI Mobile customer liability protection from the perspective of Imam Abu Hanifah's thinking. The results of the study indicate that BSI must provide protection for customer identities and contribute to the development of a digital banking customer protection model that is in line with sharia principles. Data were obtained through a documentation study of OJK consumer complaint reports, official BSI documents, and Imam Hanafi's classic literature. The analysis was carried out using the content analysis and comparative analysis methods with three stages: examining the BSI liability protection mechanism, analyzing Imam Abu Hanifah's dhaman concept, and identifying factors for the effectiveness of customer protection. This study uses a normative juridical type taken from library materials and reliable sources related to the research.